2016
DOI: 10.2217/epi.15.105
|View full text |Cite
|
Sign up to set email alerts
|

Practical Guidelines and Consideration of Using RRHP for 5hmC Detection

Abstract: 5-hydroxymethylcytosine (5hmC) is an epigenetic modification, which has been associated with gene expression in many biological contexts. Reduced representation hydroxymethylation profiling was developed as an enzymatic-based method for genome-wide 5hmC detection. It exploits β-glucosyltransferase to inhibit enzymatic cleavage of adapters ligated to a genomic library, allowing only fragments with glucosylated 5hmC residues at adapter junctions to be amplified and sequenced. The simple workflow and high sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Data deposited in GEO: accession number GSE122446. 85,86 . The raw sequencing reads were aligned to the mouse reference genome (mm10).…”
Section: Methodsmentioning
confidence: 99%
“…Data deposited in GEO: accession number GSE122446. 85,86 . The raw sequencing reads were aligned to the mouse reference genome (mm10).…”
Section: Methodsmentioning
confidence: 99%
“…Reduced representation 5hmC profiling (RRHP) analysis (46,47) was performed as previously described. (21) Briefly, 1 μg of DNA was processed using the RRHP 5-hmC Library Prep Kit from Zymo Research (Cat.…”
Section: Reduced Representation 5hmc Profiling Analysis and Callingmentioning
confidence: 99%
“…To assess which specific genes were losing 5hmC, and how this compared with the 5hmC observed in ATDC5 cells, we performed genomewide sequencing. Because of the scarcity of tissue material from cartilage microdissected from E17.5 embryos (see Materials and Methods section), we utilized a RRHP of CCGG sites, (46,47) which allowed us to probe the 5hmC status of a select number of sites in the mouse genome (Supplementary Table S5).…”
Section: Tet1 Loss In Growth Plates Changes the 5hmc Landscapementioning
confidence: 99%
“…Furthermore, studies have shown that 5hmC is enriched in active gene bodies (Gross et al, 2017;Mellen et al, 2012), suggesting a potential role of TET1 in transcriptional activation. We generated a TET1 knockdown cell line (A549-shTET1) for further analysis, reduced representation 5-hydroxymethylcytosine profiling (RRHP) identified 2,584 genes with a change of 5hmC in the gene body in A549-shTET1 compared with the wild-type (Petterson, Chung, Tan, Sun, & Jia, 2014;Sun, Chung, Tan, & Kim, 2016). RRHP also revealed additional differentially hydroxymethylated regions in introns rather than upstream sequence (Figure 1c).…”
Section: Mismatch Between the Level Of Promoter Methylation And Gene Expressionmentioning
confidence: 99%